Profile of Pancasila Students According to the Films Adit and Sopo Jarwo - Pramesti, Vembriantika Sekar; Muhroji, M (Universitas Muhammadiyah Surakarta, 2023)
This research is motivated by the phenomenon of non-moral actions in children. Providing character education using the Pancasila student profile, which contains six elements, is crucial for children aged 7–12 years or elementary school-age children. At this age, it is the initial foundation for providing character education to children. Elementary school-age children are easily influenced by what they see and hear, so they are easy to imitate. This research aims to describe the relevance of the profile values of Pancasila students according to the films Adit and Sopo Jarwo. The film is packaged for children and provides a positive message. This research use a qualitative method with a content analysis research design. The data collection technique uses non-participatory observation, which is carried out by observing audiovisuals and translating them into narratives. The primary data source was obtained directly from original sources from the first party, namely through the films Adit and Sopo Jarwo on YouTube. The secondary data sources are notes and journals. In this research, data analysis uses semiotic analysis with the Charles Sander Pierce approach, namely sign (a sign that refers to a person), object (something referred to by the sign), and interpretant (the meaning of the sign) introduced by Charles Sander Pierce.